Biopolymer containing phyllosilicates

CN122804026APending Publication Date: 2026-09-22TCHIBO GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580016612.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-02-22
Filing Date
2025-02-20
Publication Date
2026-09-22

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to a composition which is particularly suitable for the manufacture of food packaging. Therein, the composition can be used for the manufacture of a layer in a multi-layer packaging and comprises polyvinyl alcohol and a layered silicate, preferably micro-silica. Therein, the composition can form a gas barrier as well as a water barrier and in particular can provide excellent adhesion between other layers.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention relates to a composition particularly suitable for manufacturing food packaging. Hereinafter, the composition can be used to manufacture layers in multilayer packaging. Hereinafter, the composition can form gas barriers and water barriers, and in particular can provide excellent adhesion between other layers.

[0002] The broad and important principle of sustainability also applies to packaging materials. The use of biopolymers in packaging manufacturing is known and continues to increase, with biopolymers replacing or supplementing traditional polymers based on fossil raw materials.

[0003] Polymers based on renewable resources or biodegradable polymers are considered biopolymers. The most commonly available renewable raw material is cellulose, primarily extracted from wood, cotton, and annual plants. However, cellulose has inherent drawbacks that limit its use: poor solubility in common solvents, making its use as a coating more difficult; and a lack of thermoplasticity, which is essential for direct extrusion. Furthermore, cellulose is hygroscopic, reacting with water vapor and causing swelling. Moreover, it lacks both strong gas barrier properties and odor barrier properties. The latter, in particular, hinders the use of cellulose-based materials in packaging applications for high-moisture foods or in humid environments. To overcome these drawbacks, cellulose is combined with a hydrophobic layer. This also applies to starch-based polymers / solutions used in coatings or films.

[0004] Polyvinyl alcohol (PVOH) is another biopolymer commonly used in food packaging. PVOH is a water-soluble plastic and is biodegradable in aqueous environments. PVOH plastics are characterized by high tear resistance and high elasticity. These properties depend on air humidity because the plastic absorbs moisture. Depending on its composition, it has a controllable water solubility temperature of 5-90°C. As a thermoplastic, some types of PVOH can be processed in principle using conventional plastic processing methods, while water-soluble types can be processed in aqueous solution form. With appropriate selection of raw materials, including the addition of additives (especially plasticizers), it is suitable for film extrusion, thermoforming, injection molding, and blow molding.

[0005] Polyvinyl alcohol (PVA) is resistant to oils, greases, and organic solvents. Due to its hydrophilic properties, PVA is used as a good barrier material against greases and mineral oils. The hydrogen-bonded crystal structure between polymer chains makes PVA an excellent barrier material against oxygen, nitrogen, carbon dioxide, and organic solvents.

[0006] According to PVOH, PVOH products dissolve in water completely and without residue. In the dissolved state, they can be processed and recycled for reuse, or they can be completely degraded into water (H2O) and carbon dioxide (CO2) by the action of microorganisms and bacteria. Compared with non-degradable polymers (whether fossil-based or bio-based), water-soluble PVOH particles and products do not produce microplastics once dissolved.

[0007] Due to its excellent barrier properties against oxygen, CO2, and other polar gaseous / volatile compounds such as aromatic substances, PVOH is often used as a barrier layer in multilayer systems for food packaging. Its disadvantage is the lack of water vapor barrier properties.

[0008] Water resistance is typically improved through crosslinking. However, depending on the crosslinking density, the barrier effect against gases weakens, and the degradation rate decreases. To combine good water resistance with a high barrier level, metal chelating agents can be applied. Alternatively, a nonpolar water vapor barrier layer can be combined with a PVOH layer. However, nonpolar water vapor barrier layers can only be applied to polar PVOH to a relatively poor degree. Good adhesion can be achieved through nonpolar surface pretreatment with corona (plasma) or by applying adhesion promoters.

[0009] The object of this invention is to provide a composition containing PVOH that improves upon the shortcomings of pure PVOH while retaining its beneficial properties. Hereinafter, depending on the proportion of additives added, improved barrier properties against water or water vapor will also be achieved, while barrier properties against oxygen, nitrogen, carbon dioxide, and organic solvents will at least be maintained, or even significantly improved. Adhesion to other materials, particularly to similarly modified nonpolar materials, will be significantly improved. When manufacturing coatings of the said composition, improved process stability is achieved due to a significant reduction in foam formation and fewer defects.

[0010] At least one aspect of the above-mentioned objectives is achieved by a composition comprising:

[0011] 2-95% polyvinyl alcohol by weight,

[0012] 3-70% by weight of layered silicates or equivalent minerals,

[0013] 0-30% by weight of plasticizer and / or other additives, and optionally water.

[0014] The layered silicates exist in the form of microparticles and nanoparticles. The particles are preferably sheet-like. This means they are thin and elongated. In other words, the length and width of the particles are greater than their thickness or height.

[0015] Due to its excellent barrier properties, this composition is particularly suitable for manufacturing food packaging. However, other applications have also proven suitable, such as general protective coatings (for fruits, construction, and clothing), as an adhesion promoter or adhesive, and as barrier coatings in the packaging industry (for paper, films, and their multilayer composites). In this paper, the composition is particularly used as a barrier interlayer material in multilayer films or film-paper composites, and especially for improving barrier properties and adhesion between plastic layers of similar polarity, i.e., containing OH groups or acid groups and / or which may contain fillers. These layers can be bonded together or constructed by co-extrusion or coating / lamination. This composition is particularly advantageous in this paper because it combines excellent adhesion with improved barrier properties.

[0016] Depending on the intended use of the composition, the amounts of polyvinyl alcohol (PVA) and layered silicates can vary. Higher amounts of PVA, especially when combined with suitable plasticizers (including water), increase viscosity and elasticity, but weaken the barrier effect of mineral additives. Essentially, due to their chemical composition and the presence of numerous surface-present OH groups, layered silicates have a favorable effect on adhesion to polar substrates. Therefore, the composition may contain 2-95% PVA by weight, preferably 20-80% PVA by weight, more preferably 30-70% PVA by weight, and even more preferably 40-65% PVA by weight.

[0017] The amount of layered silicate refers to the total amount of layered silicate in the form of microparticles and nanoparticles, which may account for 3-95% by weight of the final composition, preferably 5-80% by weight, more preferably 10-70% by weight, 15-60% by weight, and more preferably 25-50% by weight.

[0018] In this paper, polyvinyl alcohol (PVOH) is a synthetic polymer of vinyl alcohol, which does not exist in the form of a free monomer. Polyvinyl alcohol is characterized by the vinyl alcohol unit [CH₂CH(OH)₂]. nTypically, polyvinyl alcohol (PVOH) is slightly branched, with a degree of polymerization of about 500 to 2500 monomers. PVOH is usually prepared by exchanging the acetate groups of polyvinyl acetate with hydroxyl groups, for example, through hydrolysis or alcoholysis. The percentage of acetate groups replaced by hydroxyl groups is the degree of hydrolysis of the resulting PVOH, characterizing the percentage of hydroxyl groups present in the PVOH relative to all possible hydroxyl groups. This invention covers possible compositions in which the PVOH has a degree of hydrolysis of 60 to 98 mol%, preferably 75 to 95 mol%, more preferably 80 to 90 mol%, and even more preferably 80 to 90 mol%, and is therefore water-soluble. Particularly preferred are PVOH with a degree of hydrolysis of 86 to 89 mol%. This invention also includes compositions in which the PVOH has a molecular weight or molecular mass of 13,000 to 80,000, preferably 15,000 to 60,000, and more preferably 30,000 to 50,000. The PVOH used preferably has good solubility at low water temperatures. Preferably, an aqueous solution of at least 4% can be prepared using the PVOH of the present invention at 20°C. This allows for rapid degradation even in seawater (4°C). Simultaneously, the PVOH should be of low molecular weight (30-50,000 D), thus dissolving very easily, quickly, and in a high proportion in water while still maintaining a processable viscosity (50% by weight at 25°C). Therefore, a large amount of mineral filler (at least a 1:1 ratio) can be incorporated while still maintaining sufficient binding effect.

[0019] By adding microparticles and nanoparticles of layered silicates, the low water barrier properties of cold-soluble PVOH (which possesses the aforementioned advantages) can be compensated for by its absolute impermeability to most gases. Thus, good barrier properties are combined with good cold water solubility. Therefore, this composition simultaneously achieves both of these advantageous properties.

[0020] Pure PVOH can only achieve high water barrier properties when using polymers that are poorly soluble in water. This results in slower degradation at higher ambient temperatures and higher costs.

[0021] Silicates whose silicate anions consist of vertices-shared SiO4 tetrahedral layers are called layered silicates (also known as leaf silicates or phyllosilicates). These layers or bilayers are not connected to each other by further Si-O bonds to form a lattice. Possible layered silicates for use in the compositions according to the invention include bentonite, montmorillonite, lithium saponite, pyrophyllite, and Al2[(OH)2|Si4O 10 Among the minerals used, ichnoble, apophyllite, muscovite, phlogopite, and talc are preferred due to their good availability.

[0022] One embodiment relates to a composition in which layered silicates in the form of microparticles and nanoparticles are present as a mixture of talc and related similar layered silicates such as montmorillonite, wherein the microparticles may consist of talc and the nanoparticles may consist of another layered silicate such as montmorillonite. Therefore, the term "layered silicate" herein generally refers to layered silicates, particularly talc, and to mixtures of at least two layered silicates.

[0023] Talc, also known as powdered talc, has the chemical composition Mg3[(OH)2|Si4O 10 Therefore, from a chemical perspective, it is a hydrated magnesium silicate.

[0024] Talc microparticles and nanoparticles can be manufactured from naturally occurring minerals using both physical and chemical methods. Physical methods involve producing particles by reducing the size of the starting material, for example, through grinding after mining (top-down method). However, talc can also be manufactured synthetically (bottom-up method). It has been found advantageous if the nanoparticles used are chemically synthesized, as this allows for a more uniform size distribution and improved stratification.

[0025] In general, high solids content can be achieved by using layered silicates in PVOH solutions. Therefore, higher layer thicknesses can be achieved, and the coating manufacturing process uses less water and is more energy-efficient. Furthermore, at comparable layer thicknesses, significantly higher oxygen barrier values ​​can be achieved compared to using pure PVOH. With a suitable pre-barrier layer, even higher water vapor barrier values ​​can be achieved. Suitable pre-barrier layers can consist of layers of polyethylene, polypropylene, ethylene-acrylic acid copolymers, polybutylene succinate, homopolymers and copolymers of polyhydroxyalkanoates (such as polyhydroxybutyrate and polyhydroxyvalerate and mixtures thereof), blends of polylactic acid and polyhydroxyalkanoates, or blends of poly(butylene adipate-terephthalate) and polylactic acid.

[0026] The inventors have discovered that layered silicates are preferably present in the smallest possible particle size and the highest possible aspect ratio. In this document, a higher concentration in the composition results in the maximum (“mechanical” barrier effect against diffusing gases in the coatings prepared therefrom. When the particle size is too small, increased aggregation of individual particles is observed due to increased interactions between active surfaces. This leads to a sharp increase in the viscosity of the composition. At this point, a uniform dispersion can no longer be formed. Therefore, nano-talc or nano-silicates can only be added with difficulty and in small amounts. When the added nano-talc is more than about 10% by weight, a gel-like solid is formed without shear. However, the simultaneous addition of micro-talc achieves both a higher talc or total solids content and a higher amount of nanoparticles. Furthermore, the mixture of the two types of particles works synergistically in improving the gas barrier properties of the composition and the films and layers made from it. One explanation for this is that the significantly smaller nanoparticles fill the gaps in the micro-talc, resulting in a denser particle packing and thus a significantly improved barrier effect.

[0027] It has been surprisingly discovered that an optimal composition can be obtained by mixing two particle sizes in a certain mixing ratio.

[0028] The advantages of this composition can be achieved through the mixture of microparticles and nanoparticles disclosed herein. Overall, a high concentration of mineral solids and a high solids content (including PVOH) in the total mixture can be achieved with a reduced increase in viscosity (compared to the case using the same amount of submicron-sized talc). Simultaneously, the homogenization of the particles during mixing is simplified, the foaming tendency of the composition is significantly reduced, and consequently, defects generated in the prepared layer are significantly reduced. Last but not least, the gas barrier properties of the prepared layer are improved.

[0029] For all embodiments described herein, it is preferred that the diameter of the microparticles is 0.3-5 μm and that at least one size of the nanoparticles is less than 100 nm. One embodiment of the invention relates to a composition in which the diameter of the microparticles is 0.3-10 μm, preferably 0.3-5 μm, and more preferably 0.5-4 μm. The microparticles can be characterized more precisely by their maximum particle size and average (median) particle size. In this document, it is preferred that the maximum particle size (d98%) of the microparticles is less than 15 μm, preferably less than 12 μm, and more preferably less than 10 μm. The median particle size (d50%) can be in the range of 0.5 μm to 5 μm, preferably 1 μm to 2.5 μm. The microparticles can be regular, irregular layered particles, or formed in an extended or sheet-like manner. If, for the microparticles, these microparticles are irregularly shaped particles, then the above-specified ranges refer to equivalent diameters, which are determined by comparing the physical properties of the particles, such as their settling velocity in a liquid, to those of spheres of various diameters.

[0030] In this document, the term "nanoparticle" refers to at least one particle with a size less than 100 nm. The term "nanoparticle" includes materials composed of solid particles, which may exist individually or as part of aggregates or clusters. One embodiment of the invention relates to a composition in which the nanoparticles have a maximum diameter of 1-100 nm, preferably 2-80 nm, and more preferably 5-50 nm. Nanoparticles can be more precisely characterized by their maximum particle size and average (median) particle size. Preferably, the maximum particle size (d98%) is less than 100 nm. The median particle size (d50%) can be in the range of 2 to 50 nm.

[0031] Nanoparticles may have a sheet-like shape, with one or both of their outer dimensions less than 100 nm, while the other outer dimension is in the range of 2 to 50 nm. This smaller outer dimension is preferably the thickness or height of the nanoparticle, which is therefore in the range of 2 to 50 nm, preferably 8-25 nm, and more preferably 10-20 nm. The thickness of the nanoparticle is preferably in the range of 5 to 50 nm, and the size ratio of the longest outer dimension to the thickness is in the range of 20,000 to 5, preferably 5,000 to 20, and ideally in the range of 500 to 50. This relates to single, non-agglomerated nanoparticles.

[0032] The weight percentage ratio of microparticles to nanoparticles in the compositions according to the invention can be from 60:40 to 95:5. Preferably, the range is from 70:30 to 90:10 or from 75:25 to 85:15. Particularly preferred weight percentage ratios of microparticles to nanoparticles are from 10:1 to 1:2, particularly 3:1.

[0033] Substances that make a composition or its product, such as a film, packaging, or adhesive, softer, more flexible, and more pliable are used as plasticizers. They increase plasticity, toughness, and reduce viscosity.

[0034] In the context of this invention, the plasticizer may be selected from glycerol, sorbitol, propylene glycol, triethyl citrate, and 2-methyl-1,3-propanediol. Glycerol is preferred. Plasticizers whose action is based on intermolecular interactions (primarily via hydrogen bonds in the form of OH groups) are superior to plasticizers that act through copolymerization. Therefore, as with all polymer-based polar biopolymers (cellulose / paper fibers, wood, nails, hair, skin), the contained residual (equilibrium) water also acts as a plasticizer.

[0035] In addition to the components already mentioned (PVOH, layered silicates, and plasticizers), the compositions according to the invention may also contain solvents, preferably water, and other additives.

[0036] The solvent may comprise up to 95% by weight of the composition according to the invention. Preferably, it contains up to 70% water by weight, or water content of 1-70%, 2-60% by weight, and more preferably 5-50% by weight. However, water is not essential. It primarily determines or influences the possible processing methods, particularly the method of applying the composition. Anhydrous compositions may also be used. These can be applied, for example, by melt deposition, such as using a slit die.

[0037] Other additives may comprise up to 5% by weight of the composition according to the invention. Preferably, additives not explicitly mentioned are less than 1% by weight, or the additive content is 0.1-1% by weight, more preferably 0.01-0.5% by weight. Possible additives include other polymers, anti-blocking and slip additives, stabilizers such as light stabilizers, pigments, and dyes.

[0038] Therefore, one embodiment relates to a composition, particularly a composition for manufacturing food packaging, said composition comprising:

[0039] Polyvinyl alcohol, 5-95% by weight,

[0040] Layered silicates, 5-95% by weight.

[0041] Plasticizers, calculated by weight, 0-30% by weight.

[0042] Additives, such as slip additives or anti-blocking additives, at 0-2% by weight.

[0043] The layered silicate is characterized in that it exists in the form of microparticles and nanoparticles. The composition can also be an aqueous solution or a dispersion. The water content can be up to 95% by weight. The composition is particularly suitable for depositing coatings as packaging materials such as PE films or paper. They can be used to manufacture layers in multilayer composite materials. For this purpose, water is removed. The coating is also dried after deposition onto the substrate. Therefore, details of the anhydrous composition also relate to the amount of components in the dried product or layer that can be made from the composition.

[0044] Other embodiments relate to compositions, particularly compositions for manufacturing food packaging, said compositions comprising or consisting of the following components:

[0045] 30-80% polyvinyl alcohol by weight

[0046] 20-50% by weight of layered silicates,

[0047] Plasticizer at 5-30% by weight,

[0048] Solvent content is 50-90% by weight, preferably water.

[0049] The characteristic feature is that the layered silicate exists in the form of microparticles and nanoparticles.

[0050] Other embodiments relate to compositions, particularly compositions for manufacturing food packaging, said compositions comprising or consisting of the following components:

[0051] 20-70% polyvinyl alcohol by weight

[0052] 10-50% by weight of layered silicates,

[0053] Plasticizer at 5-30% by weight,

[0054] Additives at 0-2% by weight, and

[0055] Solvent content is 0-30% by weight, preferably water.

[0056] The characteristic feature is that the layered silicate exists in the form of microparticles and nanoparticles.

[0057] Other embodiments relate to compositions, particularly compositions for manufacturing food packaging, said compositions comprising the following components:

[0058] 20-70% polyvinyl alcohol by weight

[0059] 10-50% by weight of layered silicates,

[0060] Plasticizer by weight, and

[0061] Solvent content is 0-30% by weight, preferably water.

[0062] The composition is characterized in that the layered silicate exists in the form of microparticles and nanoparticles. The composition contains no additives other than unavoidable impurities, which are less than 0.1% by weight, preferably less than 0.01% by weight.

[0063] Another aspect of the present invention is a method for preparing a composition according to the invention, the method comprising the following steps:

[0064] Provides a dispersion of layered silicate nanoparticles.

[0065] Provides a dispersion of the layered silicate microparticles,

[0066] A solution containing polyvinyl alcohol and plasticizer is provided.

[0067] A solution of polyvinyl alcohol and plasticizer is mixed with a dispersion of microparticles.

[0068] A dispersion containing nanoparticles.

[0069] The sequence of this method has been found to be particularly suitable because it produces a homogeneous mixture or dispersion and prevents excessive foaming. Essentially, the previous description of the composition also applies, to the appropriate extent, to the preparation method.

[0070] Water is preferably used as the solvent for the dispersions of nanoparticles, the dispersions of microparticles, and the solutions of polyvinyl alcohol and plasticizers. The concentration of nanoparticles can be 7-12% by weight (preferably 10% by weight) because, depending on their size / size distribution, they can form gel-like solids without shearing, i.e., without stirring. The dispersions of microparticles can be prepared in the form of concentrates, so that the desired concentration of the composition can be achieved by adding a relatively small volume of concentrate.

[0071] An alternative method for preparing the composition according to the invention includes the following steps:

[0072] Provides a dispersion of layered silicate nanoparticles.

[0073] The layered silicate is provided in powder form as microparticles.

[0074] A solution containing polyvinyl alcohol and plasticizer is provided.

[0075] The solution of polyvinyl alcohol and plasticizer is mixed with powdered particles under stirring.

[0076] A dispersion containing nanoparticles.

[0077] Using a high-speed mixer is helpful in preparing the dispersion of nanoparticles to prevent or completely dissolve agglomerates during mixing, thus forming a complete dispersion in water. This method has been found to be particularly suitable even when mixing this dispersion with a solution of polyvinyl alcohol and a plasticizer. The resulting composition is ideal for coating applications. For this purpose, the water-containing composition needs to be dried.

[0078] One embodiment of the present invention includes a composition comprising or consisting of the following components:

[0079] 1-10% polyvinyl alcohol by weight, preferably 2% PVOH by weight.

[0080] The product comprises 5-20% by weight layered silicate, preferably 8% by weight, containing nanoparticles and microparticles in a ratio of 3:1, preferably talc nanoparticles and microparticles.

[0081] 0-2% plasticizer by weight, and

[0082] It contains 80-90% water by weight.

[0083] This composition can be used to prepare very thin layers with excellent oxygen barrier properties or overall excellent gas barrier properties. However, it is quite difficult to deposit as a uniform coating, and it tends to become brittle after drying, especially when the proportion of layered silicates is very high. Including a small amount of plasticizer in the final coating can improve this.

[0084] Further embodiments of the present invention include compositions comprising or consisting of the following components:

[0085] 10-20% polyvinyl alcohol by weight,

[0086] 15-25% by weight of layered silicates,

[0087] 2-6% plasticizer by weight, and

[0088] Water content is 49-73% by weight.

[0089] Another embodiment of the invention includes a composition comprising or consisting of the following components:

[0090] 14-18% polyvinyl alcohol by weight,

[0091] Layered silicates comprising 18-22% by weight, containing nanoparticles and microparticles in a ratio of 1:3, preferably talc nanoparticles and microparticles.

[0092] 3-5% plasticizer by weight, and

[0093] Add water to bring the balance to 100%. A preferred ratio of solids in the two compositions is PVOH / plasticizer: particulate layered silicate: nanoparticle layered silicate = 4:3:1.

[0094] It has been found that this composition allows for excellent processing of high-solids content materials into coatings, multilayer films, or composites. Coatings, in particular, dry without forming defects. Products made from these compositions can be dried very easily. Therefore, inexpensive, multifunctional barrier layers can be prepared. Furthermore, this composition is suitable as a laminating adhesive for multilayer materials. These compositions, or layers made from them, adhere well to various substrates such as paper, PET film, or PE / PP film. The composition can be easily deposited, for example, by wet lamination. For non-polar substrates, pre-corona treatment or the application of additional adhesion promoters can be applied.

[0095] However, anhydrous compositions have also been found to be very suitable. These represent extrudable PVOH formulations for extrusion lamination or extrusion coating. Relevant embodiments of the invention include compositions comprising the following components:

[0096] Polyvinyl alcohol (PVA) of 50-75% by weight, preferably 60-65% by weight.

[0097] The product comprises 15-25% by weight layered silicate, preferably 18-22% by weight, containing nanoparticles and microparticles in a ratio of 1:3 to 1:20, preferably talc nanoparticles and microparticles.

[0098] 10-25% by weight of plasticizer, preferably glycerin, and

[0099] 0-5% water by weight.

[0100] In processing this composition, it can be advantageous to do so entirely or at least largely without water, as this eliminates the time-consuming and energy-intensive drying step. Water in the composition can cause bubble formation and bubbling when heated above 100°C. Anhydrous processing can also be less time-consuming and less energy-intensive, as can the preparation of the composition. On the other hand, adding water as a solvent allows for significantly greater flexibility in formulation design, resulting in a significantly higher proportion of layered silicates and thus improved barrier properties. One possible use is to produce barrier layers or barrier films by extrusion or co-extrusion with other polymers (possibly during the application of additional adhesive layers), forming multilayer materials. Combinations with PE, PP, or PET are particularly straightforward and feasible. A particularly favorable combination is one where the PE, PP, or PET layer is on the outer layer, thus encapsulating the composition of the invention. In this way, a material can be prepared that exhibits very good oxygen barrier properties due to the composition according to the invention and very good water vapor barrier properties due to the outer layer.

[0101] The composition is also suitable (e.g., by extrusion lamination) for producing a water-soluble, recyclable / recyclable layer that forms an oxygen barrier layer and is capable of bonding two other layers together. A disadvantage is the limited amount of layered silicates that can be added, which would further improve oxygen and water vapor barrier properties. Example

[0102] By using polyvinyl alcohol (Selvol) TMAn aqueous composition was prepared by mixing an aqueous solution of 205 (4% ​​by weight) with an aqueous dispersion of microparticles, and then adding an aqueous dispersion of nanoparticles to the resulting mixture. This composition contained 60% by weight H₂O, % by weight PVOH, 4% by weight glycerol, 15% by weight talc microparticles (Finntalc M05SL), and 5% by weight talc nanoparticles (Nanolay). The components were gradually mixed using a high-speed mixer. The solution was deposited as a coating on various known materials and dried. The resulting membrane consisted of 40% by weight PVOH, 10% by weight glycerol, 15% by weight talc microparticles (Finntalc M05SL), and 5% by weight talc nanoparticles (Cloisite®). The OTR (Oxygen Transmission Rate) was then measured. OTR is the steady-state rate at which oxygen permeates through individual membranes (potentially multiple layers) under specific conditions (temperature and relative humidity). The test conditions were 23°C and 50% humidity.

[0103] The following results were obtained:

[0104]

[0105] Another membrane was prepared by mixing an aqueous solution of polyvinyl alcohol (4% by weight) with an aqueous dispersion of microparticles, and then adding an aqueous dispersion of nanoparticles to the resulting mixture. The membrane contained 60% by weight of PVOH (degree of hydrolysis 87.0-89.0 mol%; viscosity (cps) 5.2-6.2, Brookfield, according to ISO 2555), 8% by weight of glycerol, 24% by weight of talc microparticles (Finntalc M05SL), and 8% by weight of talc nanoparticles. The components were gradually and uniformly mixed with the provided PVOH-plasticizer solution using a high-speed mixer. This solution was deposited as a coating onto paper (PackPro 7, 80g, Brigli & Bergmeister) and dried. The OTR (oxygen permeability) was then measured as previously described.

[0106] The following results were obtained:

[0107]

[0108] A membrane was prepared by mixing an aqueous solution of polyvinyl alcohol (4% by weight) with an aqueous dispersion of microparticles, and then adding an aqueous dispersion of nanoparticles to the resulting mixture. The membrane contained 78% by weight PVOH (degree of hydrolysis 87.0-89.0 mol%; molecular weight 30-50000 D), 2% by weight water, 5% by weight glycerol, 10% by weight talc microparticles (Finntalc M05SL), and 3% by weight montmorillonite nanoparticles. The components were gradually and uniformly mixed with the provided PVOH-plasticizer solution using a high-speed mixer. This solution was deposited as a coating onto a PE laminate (60 μm) and paper (PackPro7, 80 g, Brigli & Bergmeister) and dried. OTR (oxygen permeability) was measured as previously described.

[0109] The following results were obtained:

[0110]

[0111] Another membrane was prepared by mixing an aqueous solution of polyvinyl alcohol (4% by weight) with an aqueous dispersion of microparticles, and then adding an aqueous dispersion of nanoparticles to the resulting mixture. This membrane contained 70% by weight PVOH (98 mol% degree of hydrolysis), 12% by weight glycerol, 14% by weight talc microparticles (Finntalc M05SL), and 4% by weight talc nanoparticles. The components were gradually and uniformly mixed with the provided PVOH-plasticizer solution using a high-speed mixer, and the solution was heated to 80°C. It was observed that adding significantly more layered silicate was nearly impossible, or resulted in poor adhesion and thus a defective coating. The resulting solution was deposited as a coating onto paper (PackPro 7, 80 g, Brigli & Bergmeister) and dried. OTR (oxygen permeability) was measured as previously described. Compared to the membrane of the previous embodiment, this membrane did not dissolve without residue after 30 minutes in cold water (room temperature).

[0112] The following results were obtained:

[0113]

Claims

1. A composition, particularly a composition for manufacturing food packaging, said composition comprising: Polyvinyl alcohol, 2-95% by weight, Layered silicates, by weight 3-70%, Plasticizers at 0-30% by weight, and 0-95% water by weight Its features are, The layered silicates exist in the form of microparticles and nanoparticles.

2. The composition according to claim 1, wherein the layered silicate is Mg3Si4O 10 Talc of (OH)2.

3. The composition according to claim 1, wherein the layered silicate in the form of microparticles and nanoparticles is present as a mixture of talc and montmorillonite.

4. The composition according to any one of the preceding claims, wherein the diameter of the microparticles is 0.3-5 μm, and at least one size of the nanoparticles is less than 100 nm.

5. The composition according to any one of the preceding claims, comprising: 10-20% polyvinyl alcohol by weight, 15-25% by weight of layered silicates, 2-6% plasticizer by weight, and Water content is 49-73% by weight.

6. The composition according to any one of the preceding claims, comprising: 50-75% polyvinyl alcohol by weight, 15-25% by weight of layered silicates, 10-25% plasticizer by weight, and 0-5% water by weight.

7. The composition according to any one of the preceding claims, comprising: 1-10% polyvinyl alcohol by weight, 5-20% by weight of layered silicates 0-2% plasticizer by weight, and It contains 80-90% water by weight.

8. The composition according to any one of the preceding claims, wherein the weight ratio of microparticles to nanoparticles is 60-95:40-5.

9. The composition according to any one of the preceding claims, wherein the nanoparticles are synthesized into nanoparticles by a chemical method.

10. The composition according to any one of the preceding claims, wherein it contains up to 5% by weight of other additives.

11. A method for preparing the composition according to any one of claims 1 to 9, comprising the following steps: Provides a dispersion of layered silicate nanoparticles. Provides a dispersion of the layered silicate microparticles, Provide polyvinyl alcohol solution, The polyvinyl alcohol solution is mixed with the dispersion of the microparticles, and then... The dispersion of the nanoparticles was added.

12. The method according to claim 11, wherein the dispersion of the nanoparticles, the dispersion of the microparticles, and the polyvinyl alcohol solution all contain water as a solvent.

13. The method according to claim 11 or 12, wherein the dispersion of the nanoparticles and the dispersion of the microparticles are prepared by means of a high-speed mixer and mixed with the polyvinyl alcohol solution.

14. The method according to any one of claims 11 to 13, wherein the polyvinyl alcohol solution further comprises a plasticizer.

15. The method according to any one of claims 12 to 14, wherein in a further method step, water is removed from the solution by drying.